Synopsis: Cities and agricultural transformation in Africa: Evidence from Ethiopia - Vandercasteelen, Joachim; Tamru, Seneshaw; Minten, Bart; Swinnen, Johan (International Food Policy Research Institute, 2016)
Due to the rapid growth of cities in Africa, many more farmers are now living in rural hinterlands in relatively close proximity to cities. However, empirical evidence on how urbanization affects these farmers is scarce. To fill this gap, this paper explores the relationship between proximity to a city and the production behavior of rural staple crop producers. In particular, we analyze data from teff farmers in major teff producing areas around Addis Ababa, the Ethiopian capital. We find that farmers located closer to Addis Ababa face higher wages and land rental prices, but because they receive higher teff prices they have better incentives to intensify production. Moreover, we observe that modern input use, land and labor productivity, and profitability in teff production improve with urban proximity. This urban proximity has a strong and significant effect on these aspects of teff production, possibly related to the use of more formal factor markets, lower transaction costs in crop production and marketing, and better access to information. In contrast, we do not find a strong and positive relationship between rural population density increases and agricultural transformation – increased population density seems to lead to immiserizing effects in these settings. Our results show that urban proximity should be considered as an important determinant of the process of agricultural intensification and transformation in developing countries